Helix B surface peptide reduces sepsis‐induced kidney injury via PI3K/Akt pathway. Issue 7 (19th January 2020) - Qu, Yan; Sun, Qiang; Song, Xiaoxia; Jiang, Yan; Dong, Hai; Zhao, Wanjun; Li, Cuiping
Abstract: Aim: Helix B‐Surface peptide (HBSP) is the latest discovered erythropoietin (EPO) analogue that can retain the activity of EPO. EPO, which is widely used for treating renal anemia, has recently been proved to have protective effects on ischemia‐reperfusion injury of brain, heart and kidney. The protective effects of EPO and HBSP on cardiac function were found in rats with myocardial ischemia. However, the effect of HBSP on sepsis‐induced renal injury is still unclear. Methods: Establishment of rat kidney injury model and treated with HBSP and lipoposaccharide. Renal injury in rats was observed by hematoxylin‐eosin staining and injury index score. Levels of serum creatinine (SCr), blood urea nitrogen (BUN) and Cystatin C (Cys C) were detected using fully automatic biochemical analyzer, tumor necrosis factor‐α (TNF‐α), interleukin‐6 (IL‐6), and IL‐1β were detected by enzyme‐linked immunosorbent assay. Western blot analysis was performed to determine the role of HBSP in phosphatidylinositol 3‐kinase (PI3K)/Akt pathway. Results: Acute kidney injury (AKI) appeared after modeling, however, HBSP alleviated the pathological conditions of the kidney injury. In addition, HBSP lowered kidney injury index score in the rats, and decreased the levels of SCr, BUN, Cys C, TNF‐α, IL‐6 and IL‐1β, moreover, HBSP also showed the effect of activating PI3K/Akt pathway. Conclusion: HBSP alleviated lipoposaccharide‐induced AKI and improved kidney function of the rats with sepsis. More importantly, the effects of HBSP on lipoposaccharid‐induced AKI were realized via activating PI3K/Akt pathway. The findings in the current study provide new insights into the therapeutic mechanism for treating the disease. SUMMARY AT A GLANCE: Septic rats that were treated with helix B surface peptide (HBSP) had significantly lower kidney tissue injury score, serum creatinine and cytokines level such as IL‐6, IL‐1B in a model of sepsis associated acute kidney injury. The authors proposed that HBSP attenuates sepsis‐associated acute kidney injury via the PI3K/Akt pathway.